2022
DOI: 10.1088/2058-8585/ac49db
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of silver nanoparticle inks toward stable roll-to-roll gravure printing

Abstract: The rheological properties of silver inks are analyzed, and the printing results are presented based on the inks and roll-to-roll printing speed. The shear viscosity, shear modulus, and extensional viscosity of the inks are measured using rotational and extensional rheometers. The inks exhibit the shear thinning power law fluids because the concentration of dispersed nanoparticles in the solvent is sufficiently low, which minimizes elasticity. After the inks are printed on a flexible substrate through gravure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The web tension and pressure of the impression rollers were maintained with accuracies of ±0.3 kgf and ±0.38 psi, respectively [ 15 ]. The control system for web tension and roll impression pressure from our previously reported setup was used without modification [ 15 , 16 ]. To prevent device failure from printing position errors, we incorporated a control system based on three charge-coupled-device (CCD) cameras into our R2R gravure printing system [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The web tension and pressure of the impression rollers were maintained with accuracies of ±0.3 kgf and ±0.38 psi, respectively [ 15 ]. The control system for web tension and roll impression pressure from our previously reported setup was used without modification [ 15 , 16 ]. To prevent device failure from printing position errors, we incorporated a control system based on three charge-coupled-device (CCD) cameras into our R2R gravure printing system [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Any inconsistency in web tension or printing speed was found to affect the ink transfer process. 78) The ink rheology and printing process parameters influence the thickness, width, and surface roughness of the printed patterns, thereby affecting the characteristics of consequent dielectric and semiconducting layers that define the electrical characteristics of the printed TFTs. 59) However, since all printing processes are quite complex in practice, these factors comprehensively affect the printing process.…”
Section: Ink Rheologymentioning
confidence: 99%
“…Researchers have reported that the rheology of ink and printing conditions affect the OPRA. 78) It was also observed that the deviations in V th are due to variations in capacitance, which are in turn caused by the fluctuation in OPRA, surface roughness, and ink rheology of the printed dielectric layers. 59,83)…”
Section: Overlay Printing Registration Accuracy (Opra)mentioning
confidence: 99%
“…Mixtures containing silver, graphene nanoparticles, carbon nanotubes (CNTs), etc. are used in the fabrication of electronic devices due to their high conductivity, compatibility with substrates and excellent mechanical properties [ 24 , 25 , 26 , 27 , 28 ]. During the manufacturing process, the printed film displays non-uniform 3D morphology after solvent evaporation due to the coffee-ring effect, leading to low-resolution patterns and challenges in reproducing similar patterns, subsequently decreasing the performance of the device.…”
Section: Introductionmentioning
confidence: 99%